A Study of Pectin Biosorbent Effectiveness in Removing Lead in Water Samples Collected from Muar River - KHAIRUNNISA WADIAH MOHAMAD KHAIR; MAS RAHAYU JALIL (Progress in Engineering Application and Technology, 2026)
This paper focuses on heavy metal pollution a health risk factor and its part in aquatic life destruction. It examines extracted pectin from pomelo peels, okra pods, and roselle calyces that are agricultural waste, as a natural biosorbent for Lead (Pb) removal from the Muar River in Panchor. Initial water quality analysis reported a Pb concentration of 0.9744 mg/L, exceeding both National Standard for Drinking Water Quality and Interim National Water Quality Standard Malaysia. Pectin extraction via acid hydrolysis yielded 49.98%, 14.96%, and 27.13% for pomelo peels, okra pods, and roselle calyces, respectively. FT-IR results confirmed the existence of carboxylate groups and galacturonic acids essential for chelation. Biosorbent analysis showed that Pure Pomelo pectin achieved the highest Pb removal rate at 64.64% with an adsorbent capacity (qe) of 0.1174 mg/g. Roselle pectin maintained high dissolved oxygen levels (8.09 mg/L) while some materials increased water turbidity. Overall, the study signifies that fruit-derived pectin is an eco-friendly agent for remediating heavy metal-contaminated aquatic system.